Laser soldering and laser droplet joining for mechanical and electrical contacting of LTCC/PZT laminates - Albert, Florian; Pfeiffer, Carolin; Schmidt, Michael; Geiger, Manfred; Floessel, Markus; Michaelis, Alexander (Journal of Laser Micro Nanoengineering, 2011)
Present research in the field of active noise reduction for automotive components deals with piezoelectric laminates embedded into parts like aluminium gear boxes, car bodies or clutch housings fabricated by die casting or forced-locked insertion. Under closed loop operation, these parts are able to modify the oscillation behaviour and noise of the whole construction. Precondition for such solutions are specially designed laminates which guarantee power transmission into the parts as well as reproducible electrical and mechanical connections between the laminates and the electrical contacts. PZT actuators which are embedded in Low Temperature Cofired Ceramic (LTCC) laminates are promising for this application. This paper discusses current results of laser soldering and laser droplet joining on LTCC/PZT samples with screen printed silver pads. Laser soldered contacts allow the application of the laminates in automotive parts subjected to low thermal loads. The experimental setup for the realisation of laser solder joints on the laminates is described and the results of micrograph analysis and shear force measurements are discussed. For high temperature stable connections laser droplet joining with brazing material is used. The thermal energy of the applied molten droplets needs to be adjusted in order to prevent the laminates and their pads from being damaged. The process technology and results for the creation of crack-free connections are described.
Created from Fastlane, Scopus look-up
Keywords: Laser droplet joining; Laser soldering; LTCC/PZT laminates